Environmental Issues and Biofuel Production Prospects in the Central Federal District of Russian Federation - TITOVA, Ekaterina S.; RATNER, Svetlana V. (Journal of Environmental Management and Tourism; Vol 10 No 5 (2019): JEMT Volume X Issue 5(37) Fall 2019, 2019)
Growing attention to renewable energy in Russia is largely determined by the fact that some of these technologies allow the processing of anthropogenic waste and by that reduce environmental damage. Heterogeneous economic, geographical and climatic conditions for the Russian Federation regions development set the scientific task of studying regional practices, taking into account the existing programs for the renewable energy production development. The objectives of this study were exploring innovative approaches already used in leading countries of biofuel production organizing as one of the way to ensure sustainable development, as well as an analysis of existing experience and prerequisites for using such approaches in certain regions of the Russian`s Central Federal District. As an example, considered some existing indicators and programs for the fuel and energy sectors development, as well as the results of the individual enterprises in the Belgorod, Voronezh, Yaroslavl and Kostroma regions long-term activities, which use innovative approaches to the production of biofuels. Taking into account various regulatory documents recommendations, including instructions of national standards for innovation management, a number of factors for the effective implementation of innovations in the biofuel production are highlighted. Particular attention is paid to the biofuel production importance for the solid industrial, agricultural and household waste, containing organic compounds, processing as a promising way to protect the environment from anthropogenic pollution, which may be the key to the existing environmental conditions maintaining.